2018
DOI: 10.3390/w10050559
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Straw Amendment on Soil Physicochemical Properties and Crop Yield on a Consecutive Mollisol Slope in Northeastern China

Abstract: Straw amendment (SA) can be used to increase soil organic matter and decrease dioxide carbon emissions. However, the impact of SA on the crop yield is still subject to debate in different areas. In this study, soil temperature (ST), soil moisture (SM), soil bulk density, soil-available-nitrogen (AN), soil-available-phosphorus (AP), crop growth and yield were measured in SA and NSA (no straw amendment) at slope positions of a 130-m-long consecutive Mollisol slope during the maize (Zea mays) growth stages in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Additionally, SWC and SWS were noticeably higher under NTS and CTS treatments due to retention of residues. Residues mainly improved the water availability and infiltration [71]. Our results are in agreement with [47], who declared that residues application markedly improved SWC and SWS.…”
Section: Effect Of Treatments On Soil Physical Propertiessupporting
confidence: 92%
“…Additionally, SWC and SWS were noticeably higher under NTS and CTS treatments due to retention of residues. Residues mainly improved the water availability and infiltration [71]. Our results are in agreement with [47], who declared that residues application markedly improved SWC and SWS.…”
Section: Effect Of Treatments On Soil Physical Propertiessupporting
confidence: 92%
“…The application of organic mulches and amendments to the soil is a well-recognized water saving practice. Zhang et al [13] provided evidence that straw amendments applied to a sloping field of northeastern China reduced water losses by evaporation and increased soil organic matter while decreasing carbon dioxide emissions. In addition, it positively influenced the dynamics of available nitrogen and phosphorous in soil.…”
Section: Innovation Issues At Local Scalementioning
confidence: 99%
“…Soil temperature is an important ecological factor for determining water and nutrient uptake by crop root systems [24]. Previous studies have shown the beneficial regulating effects of organic amendments on soil temperature for high soil organic carbon, soil available water content, and soil water holding capacity [4,25,26]. Consistent with these findings, MWS reduced the maximum soil temperature and raised the minimum soil temperature, while it significantly reduced the mean soil temperature at 0-10 cm depth compared to CO in our study (Figure 2).…”
Section: Soil Temperature Responses To the Organic Amendmentsmentioning
confidence: 99%